Synthesis, Crystal Structure, DFT Studies and Evaluation of the Antioxidant Activity of 3,4-Dimethoxybenzenamine Schiff Bases - Ahmad Nazif Aziz (Molecules, 2014)
Schiff bases of 3,4-dimethoxybenzenamine 1–25 were synthesized and evaluated for their antioxidant activity. All the synthesized compounds were characterized by various spectroscopic techniques. In addition, the characterizations of compounds 13, 15 and 16 were supported by crystal X-ray determinations and their geometrical parameters were compared with theoretical DFT calculations at the B3LYP level of theory. Furthermore, the X-ray crystal data of two non-crystalline compounds 8 and 18 were theoretically calculated and compared with the practical values of compounds 13, 15, 16 and found a good agreement. The compounds showed good DPPH scavenging activity ranging from 10.12 to 84.34 μM where compounds 1–4 and 6 showed stronger activity than the standard n-propyl gallate. For the superoxide anion radical assay, compounds 1–3 showed better activity than the standard.